Pengaruh Leverage, Komite Audit dan Kualitas Audit Eksternal Terhadap Penghindaran Pajak - Meilinda, Anisah; Indriani, Poppy (Universitas Batanghari Jambi, 2024)
The income that a country has in developing the economy in each region is generated by the APBN budget, one of which is revenue from taxes, where taxes are a sector that dominates the main source of state income and can be used for people's welfare. However, there is often an inappropriate target in tax management, where there are still taxpayers who carry out tax avoidance actions which can have an impact on the stability of the country. Tax avoidance is often caused by taxpayers having higher debt than capital, as well as other things such as the performance of external auditors which is not optimal and lack of supervision by the audit committee every time a financial report is submitted. This research aims to identify leverage, audit committee and external audit quality variables on tax avoidance in manufacturing companies listed on the IDX within a period of 4 years, namely 2019 - 2022. This research uses objects on 22 companies listed on the Stock Exchange Indonesian Effect 2019-2022, analysis technique using panel data regression using the fixed effect model (FEM). The results show that overall the quality of external audits and audit committees has a positive influence at a significance level of 0.05, while leverage (DER) with a probability value of 0.88 > 0.05 means that companies that are the object of research tend to have higher liabilities and tax burdens. . Apart from that, this research, from the results of the unit root test and cointegration test, can be interpreted as saying that the variables used are appropriate and have a long-term nature and are supported by the absence of elements of classical assumptions. Apart from that, the value of r-square is 0.7394 (73.94%) where the remaining 26.06% is influenced by types of variables outside this research such as the tax gap, capital buffer and other financial ratios.